Trust in the dentist and intention to return: a cross-sectional study (Revista Contexto & Saúde, 2025)
Objectives: This study aimed to analyze patients’ confidence and intention to return to the dentist who last performed dental care, and to verify associated factors. Methods: From a cross-sectional study, the sample consisted of 378 patients aged 15 years or older who underwent dental treatment in different locations in a city in southern Brazil. A self-administered questionnaire regarding affection and cognition with the dentist, confidence, and intention to return to dental service, life satisfaction, and sociodemographic questions formed of the data collection instrument. Results: Data were analyzed using a binary logistic regression model. Patients who had affection and cognition with their dentist (PR=2.01; 95%CI 1.73-2.32) and were satisfied with their lives were more likely to trust their dentist and return for dental care (PR=1.11; 95%CI 1.05-1.23). The positive aspects of cognition and affect for the dentist as well as life satisfaction influence the confidence in, and intention to return to the professional who performed the last dental procedure. Conclusions: The subjectivities of dental care and treatment, as well as professional behavior, are approaches that must be incorporated during dental training.
Keywords: Trust; Affect; Cognition; Dentist-Patient Relations; Dental Offices